Cloning of an Avian Antithrombin: Developmental and Hormonal Regulation of Expression - Tejada, Max L; Deeley, Roger G (Thrombosis and Haemostasis, 1995)
We present the complete amino acid sequence of a non-mammalian antithrombin together with a structural comparison to its mammalian homologs. In the majority of cases, but not all, the analyses indicate high degrees of primary structural identity within regions of predicted or demonstrated functional importance. We have also taken advantage of the avian model to define the ontogeny of antithrombin mRNA expression. Northern analyses indicate chicken antithrombin mRNA levels to be detectable in the liver early during development and increase to reach adult levels just prior to hatching. Although no sex-dependent differences in antithrombin mRNA levels were detected, the administration of estrogen to male roosters was observed to cause a 3-fold decrease in antithrombin mRNA levels, suggesting that the hormone may alter circulating antithrombin levels via a pre-translational mechanism.